Deposição de calda aplicada em folhas de cafeeiro com diferentes volumes e pontas de pulverização - Silva, João Eduardo Ribeiro da (2013)
Coffee crop is an important agricultural and economic activity in Brazil. The country is the greatest coffee producer and exporter, and has in the state of Minas Gerais the major national producer. One of the biggest problems faced by coffee farmers is the susceptibility of the plants to several pests and diseases. Among these, the leaf-miner, considered a key pest of the crop, occurs in almost all producing regions. Pest management has been successful by employing chemical control; however, the crop presents many challenges for application technology, such as dense foliage development and variations in the canopy. This study evaluated spray deposition on leaves of coffee arabica (Coffea arabica L.), and its loss to soil resulting from the pulverization of two application volumes and two spray nozzle types. The work was conducted at Glória s farm, property of the Federal University of Uberlândia, Uberlândia-MG, in 11 years old coffee arabica cultivar Catuaí IAC 99, in september 2012. The experiment was a 2x2 factorial, with two nozzles, (ATR) hollow cone and (TVI) hollow cone with air induction, and two volumes, 200 L ha-1 and 500 L ha-1. Brilliant Blue coloring was added to the tank mixture, at a fixed concentration of 300 g ha-1. Leaves were collected from upper and lower halves of plant canopies and glass slides were positioned on the ground under the plant canopy to collect spray drippings. The concentration contained in the samples was determined by light absorption spectrophotometry. Also, a study of statistical process control (SPC) was conducted, allowing the evaluation of the behavior of the variables in their repetitions within treatments. The use of hollow cone tips with air induction together with greater spray volume (500 L ha-1) was a good option for spray deposition in coffee leaves. At the lower half of the canopy, spray deposition was similar using both 200 L ha-1 and 500 L ha-1, which demonstrates the feasibility of using the reduced spray volume. The hollow cone with air induction nozzle resulted in greater losses to the soil. The analysis of the control charts (SPC) related to treatments showed that no great variability among the sampling points was found, indicating good quality standard from the statistical point of view.